SIMULATION OF THREE DIMENSIONAL FLOW OVER DARRIEUS WIND TURBINE TYPE-H - RISATRIO (NIM : 13606008); Pembimbing : Dr. Firman Hartono ST. MT. , ALIF
The increasing human population causing the world's dependence for energy becoming more vital. However, most of energy w use still dependent on a nonrenewable energy source. Wind energy as a source of renewable energy has tremendous potential to be exploited. One way to harness the potential of wind energy is to use wind turbines as a device of converting wind power into electrical power. Various research on wind turbine technology recently has more conducted by the researchers. Some of them are research on vertical wind turbines. Three-dimensional simulation flow over the turbine Darrieus type-H is one of them. CFD simulations carried out in three dimensions using the program ANSYS-CFX. The results of the simulation will be analyzed and compared with simulations that have been done before. But there has been no experimental testing of this wind turbine configuration so that the results of the analysis can not be validated. The steps in detail will be presented further in this report. Ultimately the results obtained are inconsistent with some references. Although there are indications that similar to the results of the previous two-dimensional CFD analysis, but magnitude and the tendency of these simulation results do not follow the laws of fluid in general. The conclusion that most likely is a mistake in the modeling of the simulation, so that what is analyzed is not in accordance with actual conditions.